2020
DOI: 10.1111/cxo.12936
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, perspectives and clinical practices of Australian optometrists in relation to childhood myopia

Abstract: Background The aim was to investigate the understanding of Australian optometrists in relation to myopia, its natural history and associations with vision‐threatening ocular disease, self‐reported clinical diagnosis and management approaches for childhood myopia, engagement with adult caregivers, and utilisation of information to guide practice. Methods An online survey was distributed to Australian optometrists (n = 4,124). Respondents provided information about their demographics (for example, gender, age, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
56
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(70 citation statements)
references
References 42 publications
(73 reference statements)
3
56
2
Order By: Relevance
“…In an early retrospective analysis published in 1957, Morrison [3] reported no refractive progression in seven to 19-year-old children with previously steadily progressing myopia who wore flat-fitting rigid corneal lenses (~2.00 D flatter than the flattest corneal meridian) for at least 18 h a day. Since the late 1990's, ortho-k has been perceived by ECPs to be one of the most effective methods of myopia control [15][16][17][18] (see Section 8). In 2005, half a century after Morrison's clinical observations [3], a prospective single-arm intervention study suggested that ortho-k had the capacity to modulate myopia progression in children, relative to a historical control group of single-vision distance spectacle lens wearers [19].…”
Section: Historical Overviewmentioning
confidence: 99%
“…In an early retrospective analysis published in 1957, Morrison [3] reported no refractive progression in seven to 19-year-old children with previously steadily progressing myopia who wore flat-fitting rigid corneal lenses (~2.00 D flatter than the flattest corneal meridian) for at least 18 h a day. Since the late 1990's, ortho-k has been perceived by ECPs to be one of the most effective methods of myopia control [15][16][17][18] (see Section 8). In 2005, half a century after Morrison's clinical observations [3], a prospective single-arm intervention study suggested that ortho-k had the capacity to modulate myopia progression in children, relative to a historical control group of single-vision distance spectacle lens wearers [19].…”
Section: Historical Overviewmentioning
confidence: 99%
“…Despite these advances, the majority of progressive myopes are still prescribed single vision spectacles, especially in countries outside of Asia 23 26 . There is a scarcity of published literature that examines the possible reasons for the very limited uptake of active myopia management.…”
Section: Introductionmentioning
confidence: 99%
“…The lens designs that have been assessed incorporate either concentric rings of plus power, peripheral optical zone(s) with add power and lens designs that incorporate non-monotonic variations in power, varying in both myopic and hyperopic directions. However, in spite of these significant advances, contact lens fittings for myopia control are limited to only about 2-5 % of the total contact lens fittings, with single vision spectacles remaining the most popular myopia management modality [451,452].…”
Section: Myopia Controlmentioning
confidence: 99%
“…One of the reasons for low uptake of soft contact lenses for myopia management relate to perceptions on efficacy, with soft lenses ranking behind orthokeratology and pharmaceutical options in terms of perceived efficacy by ECPs worldwide [451,452]. Despite this, the myopia control field is growing and research considering innovative and improved approaches to slow myopia is of great interest.…”
Section: Myopia Controlmentioning
confidence: 99%